The Problem of a Body: ldentification and ldentity in Antanas Škėma's „Isaac" - Juškevičiūtė, Rima (Respectus Philologicus, 2001)
This interpretational work attempts to reveal the functioning of body images and toward the Other oriented postholocaust existential issue in Antanas Škėma's short story Isaac using the deconstructive methods of phenomenology and psychoanalysis. Self-identification possibilities are revealed through the study of the intertext by using images of a body. The ability of ego to construct its own narrative (A. Giddens) is chosen on the basis of identity construction analysis. The author records untypical existential experience of war in Lithuanian literature by making a connection between a historical glance into the past and the conception of death.
Keywords: identification; identity; the Other; own body; deconstruction; intertextuality; series (G.Deleuze); event; memory